Didactic unit to promote orality and writing from local history - González López, Olga Mariela (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This research project aims to develop a didactic unit for fourth and fifth grade students, in order to improve communication skills, emphasizing orality and writing through the recognition of the local history of the “Gaunza Abajo” school branch in Guateque (Boyacá). The proposal is framed under the socio-criticalparadigm, Qualitative Research approach and Action Research design, proposed in four stages, starting with a diagnosis to determine the level of development that students have, then design and development of the teaching unit based on quality referents emanating from the Ministry of National Education (MEN, 2010), after the application, execution and analysis; finally, socialization through a radio station. The didactic unit allowed children to be the architects of learning in interaction with the context. In this way, students’ progress is evident in the oral-writer process.